Rapid Assessment of Diverse Trichodermal Isolates of Indonesian Origin for Cellulase Production - Fahrurrozi, Fahrurrozi; Ratnakomala, Shanti; Anindyawati, Trisanti; Lisdayanti, Puspita; Sukara, Endang (ANNALES BOGORIENSES, 2010)
Trichoderma is a well -known candidate to be promoted as cellulase producerÂ  for the hidrolysis of lignocelluloses that containÂ  inÂ  woodyÂ  biomass. TheÂ  number of trichodermalÂ  isolatesÂ  in ourÂ  laboratory collectedÂ  from diverse ecosystem types in Indonesia increases significantly during the last 5 years. It is our aim to assess the cultures for its ability in producing cellulase. Sixty-six trichodermal isolates used in this experiment are obtained from Biotechnology Culture Collection (BTCC), Research Center for Biotechnology, Indonesian Institute of Sciences(LIPI) Â The 31 isolates were isolated from District of Liwa (South Sumatra, Indonesia) and the 35 isolates from District of Maros (South Sulawesi, Indonesia). TheÂ  isolates were screened qualitatively,Â  7Â  isolatesÂ  fromÂ  Liwa and 12Â  isolates from Maros showed cellulolytic activity. From the results of quantitative test, two strainsÂ  (ID08-T004 and ID08-T63) showed the higher cellulolytic activity among the selected strains, 133.5 and 133.5 U/ml, respectively.Â  TheseÂ  extracellularÂ  enzymesÂ  wereÂ  characterizedÂ  theirÂ  temperatureÂ  andÂ  pHÂ  optimum.Â  The temperatureÂ  optimumÂ  forÂ  bothÂ  enzymesÂ  wasÂ  theÂ  same,Â  50ï°C,Â  withÂ  activityÂ  213.6Â  U/mlÂ  forÂ  enzymeÂ  extracted from ID08-T004 and 197.3 U/ml for enzyme from ID08-T0063. The pH optimum was pH 5 of ID08-T004 with activity137.7 U/ml and pH 6 for ID08-T063 with activity 75.0 U/ml. The enzymes from ID08-T004 and ID08-T063 were stable in their temperature and pH optimal condition even after 90 minutes incubation with activity 179.0 U/ml and 86.7 U/ml, respectively. The enzyme stability was approximately 150 minutes for both enzymes in the temperature and pH optimum. Â  Key Words: Trichoderma, cellulase, Culture Collection